(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This article analyses the neo-institutionalisation of mental illness from a sociological perspective, based on research conducted in November 2024 at the OPZ in Geel, Belgium. It focuses on the concept of social belonging in psychiatry as a means to counter cyclical relapses into new institutional forms. After defining neo-institutionalisation and examining the Italian case (Law 180/1978), the text explores Geel as a model of family foster care. The findings suggest that communi-ty education and awareness-raising are crucial tools for strengthening long-term deinstitutionalising practices.